FATE AND EVENT KNOWLEDGE IN THE CREATIVITY OF ESHKABIL SHUKUR - Abdurahmonova Uldona Abdujapbarovna (Bright Mind Publishing, 2025)
In this article, the knowledge of fate and event in the poetry of Eshkabil Shukur is discussed in the poem "Three Wisdoms of Knowledge" in the series "Nasoyim ul-Muhabbat" poem "Sultanism <> Gadolik = science"; "man <> the afterlife = repentance"; "Wonder <> Soul Bird = Love"; "Two Worlds <> One Language = Truth" explored in artistic contrasts.
Keywords: Science, metaphor, symbol, self-symbol, knowledge of destiny and event, sultanate, greed, wonder, truth, artistic contrast.